Sammenligning av fettoksideringen og energiforbruket under intervalltrening og kontinuerlig trening blant godt trente menn - Brovold, K. V. (2011)
Background: This study was conducted on the basis of the limited literature on fat metabolism among well-trained men during high-intensive training. Purpose: We have: 1) quantified the total energy expenditure and the substrate oxidation among well-trained men, during a high-intensity interval session and a continuous session matched for average workload, 2) compared the relative fat oxidation during a high-intensity interval session and a continuous session to the maximal fat oxidation rate identified by the Fatmax protocol of Achten, Gleeson and Jeukendrup and 3) compared the energy expenditure after a highintensity interval session and a continuous session, based on EPOC. Methods: Nine welltrained male runners (VO2max: 68.1 + 3.6 ml.kg-1.min-1) completed preliminary testing followed by an interval session and a continuous session in randomised order. Blood lactate (La-) and blood gases were measured. The sessions lasted 48 minutes at a 1.7% incline. Individual running velocities were calculated corresponding to 40, 65 and 90% of VO2max. Results: Fat oxidation accounted for 17 + 8% (0.27 + 0.11 g.min-1) of the total energy expenditure during the interval session. The blood gases stabilized from work bout one to six. La- rose moderately, but significantly from work bout three to six. Fatmax was located at 65 + 8% of VO2max (0.55 + 0.17 g.min-1). Energy expenditure based on EPOC was higher, but not significant for the continuous session compared to the interval session. Conclusion: The subjects oxidized significant amounts of fat during a high-intensity interval session. The energy expenditure based on EPOC was greater, but non significant after the continuous session compared to the interval session.